Cell-permeant NAADP: a novel chemical tool enabling the study of Ca2+ signalling in intact cells. - Parkesh, R; Lewis, A; Aley, P; Arredouani, A; Rossi, S; Tavares, R; Vasudevan, SR; Rosen, D; Galione, A; Dowden, J; Churchill, G (2008)
NAADP (nicotinic acid adenine dinucleotide phosphate) is a recently discovered second messenger, and as such, we have much yet to learn about its functions in health and disease. A bottleneck in this basic research is due to NAADP, like all second messengers, being charged to prevent it from leaking out of cells. This makes for effective biology, but imposes difficulties in experiments, as it must be injected, loaded via liposomes, or electroporated, techniques that are highly technically demanding and are possible only in certain single cell preparations. For the better understood second messenger inositol 1,4,5-trisphosphate, great success has been obtained with cell-permeant derivatives where the charged groups are masked through esterification. We now report NAADP-AM as a cell-permeant analogue of NAADP that is taken up into cells and induces NAADP-mediated Ca(2+) signalling. NAADP-AM is a powerful chemical tool that will be of enormous biological utility in a wide range of systems and will greatly facilitate research into the role of NAADP in health and disease.